TO EXAMINE FREQUENT MINING TECHNIQUE BY USING GRAPH MINING - K, Suresh; M, Geethika M; M, Akshatha H (International Journal of Psychosocial Rehabilitation, 2020)
requent pattern mining devises a very remarkable applicability. There are different reallife databases. Several algorithms have been established to discover the frequent itemsets grounded on different parameter and analysis. But, it acts more challenging to catch the definite exciting patterns as every patterns consider different position. A method for finding frequent itemsets with graph mining technique is introduced. There are several algorithms to find frequent patterns but the main drawback is that it all takes longer time. Inorder to solve this problem graph mining technique is used. Instead of using tree, here graph mining method is used to increase algorithm accuracy. In proposed technique the computation time and data size will be reduced.